1996
DOI: 10.1002/j.2048-7940.1996.tb00840.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Self-Efficacy Theory to Educate Patients with Chronic Obstructive Pulmonary Disease

Abstract: The predominant debilitating symptom in patients with chronic obstructive pulmonary disease (COPD) is shortness of breath. Self-efficacy theory has been used in a case study approach to begin examining the expectations of a patient with COPD who attended a pulmonary education program. Mr. M. was selected for the case study because his condition typifies many of the problems encountered by patients with COPD. Mr. M.'s self-confidence in managing his breathing difficulty was measured by using the COPD Self-Effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The findings were consistent with the work of Kaplan et al. (1984), Scherer and Shimmel (1996), Zimmerman et al. (1996), Scherer and Schmieder (1997), and Scherer et al.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings were consistent with the work of Kaplan et al. (1984), Scherer and Shimmel (1996), Zimmerman et al. (1996), Scherer and Schmieder (1997), and Scherer et al.…”
Section: Discussionsupporting
confidence: 91%
“…From the results of the regression model, we found that the factors contributing to self‐efficacy included ‘telephone follow‐up group’, ‘(attended) pulmonary rehabilitation’, ‘(not) smoking’, and ‘(less) health care use’. The literature did show that attending an intensive rehabilitation programme could enhance the self‐efficacy of patients with COPD (Scherer & Shimmel 1996, Zimmerman et al. 1996, Scherer & Schmieder 1997, Scherer et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-effi cacy refers to a person's confi dence in being able to perform an action or behaviour or to alter thoughts (Bandura, 1977(Bandura, , 1997. The importance of self-effi cacy in facilitating adjustment and coping in adults with chronic disease, such as COPD, is well documented in the literature (Scherer and Shimmel, 1996;Woodard and Berry, 2001;McCathie et al, 2002;Marks et al, 2005). Therefore, an important outcome of occupational therapy for adults with COPD is to change patients' self-effi cacy regarding managing dyspnoea and other symptoms (Guyatt et al, 1999).…”
Section: Discussion and Implications For Occupational Therapy Practicementioning
confidence: 97%
“…A substantial body of literature demonstrates the importance of patient education in health care. The inclusion of structured educational opportunities in the rehabilitation of chronically ill people has demonstrated that education is a vital step in the process of adjusting to the effects of chronic health conditions (American Cancer Society, 1994; Johnson, 1982; Scherer & Shimmel, 1996). Educational programs can also reduce the severity of depression and emotional distress (Dodd, 1997; Zimmerman, Brown, & Bowman, 1996).…”
Section: Overviewmentioning
confidence: 99%